2017
DOI: 10.3415/vcot-16-05-0071
|View full text |Cite
|
Sign up to set email alerts
|

Kirschner wire fixation of Salter-Harris type IV fracture of the lateral aspect of the humeral condyle in growing dogs

Abstract: Fracture of the lateral aspect of the humeral condyle in growing dogs can be successfully treated by multiple transcondylar convergent or parallel Kirschner wires, resulting in adequate fracture healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 22 publications
6
32
0
Order By: Relevance
“…In 85% of cases, the dogs for which long‐term owner assessments of function were obtained had excellent limb use with no evidence of lameness. These results were comparable to previous reports in which success rates ranged from 67% to 92%, corroborating that dogs have a good prognosis for excellent return to function following unicondylar humeral fracture stabilisation, and this was also reflected in the owners’ satisfaction with the outcome of the surgery.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In 85% of cases, the dogs for which long‐term owner assessments of function were obtained had excellent limb use with no evidence of lameness. These results were comparable to previous reports in which success rates ranged from 67% to 92%, corroborating that dogs have a good prognosis for excellent return to function following unicondylar humeral fracture stabilisation, and this was also reflected in the owners’ satisfaction with the outcome of the surgery.…”
Section: Discussionsupporting
confidence: 88%
“…Of the 28 fractures that had adequate clinical and radiographic follow‐up evaluations, 75% healed without complications and 14% healed with minor complications. The minor complication rate in this study was lower than that reported in other studies assessing unicondylar humeral fractures stabilised via limited open or open reduction (21–35%) and similar (9%) to that reported by a study in which fractures were stabilised in a closed fashion . The major complication rate of 11% in this study was higher than reported in other studies (0–3%) in which unicondylar humeral fractures were stabilised by either via limited open or open reduction, but was comparable (9%) to fractures stabilised in a closed fashion .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Methods of repair include wire, 10 rush pins, 11 transcondylar screws, 12 Kirschner wires (K‐wires), 13 self‐compressing Orthofix pins, 14 cannulated screws, 15 and closed reduction with subsequent internal fixation 16 . A transcondylar screw in lag fashion with a supracondylar point of fixation to prevent rotation has been most commonly performed 17‐19 .…”
Section: Introductionmentioning
confidence: 99%
“…Several limitations of using gliding hole lag screws have been reported in fracture repair, such as excessive loss of bone, screw thread stripping and more soft-tissue injury related to the extensive surgical approach. 4 In addition to the standard use of a transcondylar lag screw, several techniques have been described for condylar fracture fixation in small animals, such as the use of Kirschner wires, 5,6 position screw 2 and specially designed selfcompression implants. 7,8 However, limitations and potential complications also exist with these methods, such as higher cost, limited instrument size or the lack of evidence-based studies in medium-and large-sized dogs.…”
Section: Introductionmentioning
confidence: 99%